Effect of Mutations in GvpJ and GvpM on Gas Vesicle Formation of Halobacterium salinarum - Jost, Alisa; Knitsch, Regine; Völkner, Kerstin; Pfeifer, Felicitas (Frontiers in Microbiology, 2021)
The two haloarchaeal proteins, GvpM and GvpJ, are homologous to GvpA, the major gas vesicle structural protein. All three are hydrophobic and essential for gas vesicle formation. The effect of mutations in GvpJ and GvpM was studied in Haloferax volcanii transformants by complementing the respective mutated gene with the remaining gvp genes and inspecting the cells for the presence of gas vesicles (Vac+). In case of GvpJ, 56 of 66 substitutions analyzed yielded Vac- ∆J+Jmut transformants indicating that GvpJ is very sensitive to alterations, whereas ten of the 38 GvpM variants resulted in Vac- ∆M+Mmut transformants. The variants were also tested by split-GFP for their ability to interact with their partner protein GvpL. Some of the alterations leading to a Vac- phenotype affected the J/L or M/L interaction. Also, the interactions J/A and J/M were studied using fragments to exclude an unspecific aggregation of these hydrophobic proteins. Both fragments of GvpJ interacted with the M1-25 and M60-84 fragments of GvpM, and fragment J1-56 of GvpJ interacted with the N-terminal fragment A1-22 of GvpA. A comparison of the results on the three homologous proteins indicates that despite their relatedness, GvpA, GvpJ and GvpM have unique features and cannot substitute each other.